Implementação da rede de atenção psicossocial (RAPS) no contexto na política de saúde mental do município de São Carlos/SP (2010-2015) - Oliveira, Fernando Calzavara de (2016)
The Ordinance No. 3088, of December 23, 2011, establishes the framework the Unified Health System (SUS) and the mental health policy in Brazil formation guideline and implementation of psychosocial care network .Considering the need for the SUS: 1) encourage the formation of a network integrated, coordinated and effective mental health in different parts of attention to meet people with suffering or mental disorder and needs arising from the consumption of alcohol, crack and other drugs; besides 2) expand and diversify the provision of services to the same population, we seek through this research to analyze to what extent and how this policy is being implemented in the context of mental health policy of São Carlos city at São Paulo State. However, the objective of the study was to verify whether they are being implemented innovative means of intersectoral management, integrated and articulated, that confer efficacy to psychosocial care, along the lines adopted by SUS for mental health, and identify what are these possible mechanisms in order to make recommendations for procedures the gain in efficiency of decentralized management of this policy can be replicated in other cities depending on the higher or lower specificities and obstacles discovered. From the identification fragmentation characteristics of the same during the process of implementation, it was possible to create a picture in order to identify possible variables related to this current configuration. The methodology used was embedded single case study (Yin, 2005), and data collected through empirical observation, semi structured interview script application with managers who coordinate services and agents implementers, and through documentary survey of the records Psychosocial Care Center Alcohol and Drugs- CAPS AD from Sao Carlos city, between 2010 the 2012. Finally, we concluded that the implementation of RAPS policy in São Carlos city is weakened because of: 1) his condition current training, 2) the effects on structuring of the different models of mental health care that overlap, and 3) the action actors who produces conflict and not cooperation.